Psalm 106 and Chaos Theory: A Study of Israel’s Covenant Infidelity and Yahweh’s Sovereign Control - Ndoga, Sampson (Journal for Semitics, 2024)
Book IV of the Psalter ends on an anticipative note despite Israel’s chaotic history of serial failures. The psalmist foregrounds Yahweh’s acts of covenantal faithfulness as expressions of perennial divine faithfulness, favour, and forgiveness against Israel’s perpetual disloyalty. By reading Israel’s history through the mathematical conception of chaos as predictable patterns of behaviour managed under the outworking of divine purposes, what seemingly appear as random acts of rebellion become modelling of behaviour that Yahweh always has under control. Starting from Book III which closes on a similar note of despondency by citing the total collapse of the Davidic covenant, Yahweh is not out of sorts as the editors of the Psalter carefully arrange their material to demonstrate the triumph of the divine prerogatives. By duplicating the closures in books III and IV of a history of failures, the redactors show the two constants in the development of the psalm motifs: perennial divine faithfulness despite Israel’s unfaithfulness. Psalm 106 is based on an arrangement to manage the re-reading of this negative history in a way that enables Book IV to not only close on a positive note but also pave the way for Book V to advance the collection towards a climax.
paid
Keywords: Chaos; book iv; historical psalm; psalter; redactional arrangement